Ecological aspects of Telmatobius atacamensis (Anura: Telmatobiidae), a microendemism from the Puna, Salta-Argentina - Acosta, Rebeca (2020)
Telmatobius atacamensis is a microendemic threatened anuran of the Puna of Salta, Argentina. In this study, we identify reproduction nuclei and we characterize the anurans populations. To do this, an annual sampling was made in Los Patos and San Antonio rivers and we selected ten sampling sites. We measured pH, temperature and electrical conductivity at each site. The visual encounter survey (VES) was used in order to identify the individuals. Three categories of larval development were established: prometamorphic (G1), premetamorphic (G2) and metamorphic climax (G3). We found a total of six reproductive nuclei, four in San Antonio River and two in Los Patos River. The individuals were located in underwater shelters with a low range of electrical conductivity and in a wide range of temperature while the pH was alkaline. The relative abundance at the larval stages were significantly different between the rivers (ANOVA F= 109.41 p<0.000), the highest abundance was detected in Los Patos River. The adults were sampled in both rivers during the year with significant differences in their abundance (T= 19.83 p<0.0001), being the highest in Los Patos River. This study would contribute significant information to the assessment of the current conservation status and the objective development of strategies for the design of effective monitoring, further population comparisons and species protection.